First record of the genus Anisogammarus (Crustacea, Amphipoda, Anisogammaridae) from Korea, with description of a new and a newly recorded species - Nam, Yu-Ri; Choi, Jae-Hong; Kim, Young-Hyo (Zootaxa, 2026)
This study aims to discover and document amphipods from Korea, contributing to the clarification of the Korean amphipod taxonomy. As part of this effort, a new species and a newly recorded species of the anisogammarid amphipod genus Anisogammarus were collected from the East Sea of Korea. The new species, A. donghaensis sp. nov. is morphologically similar to A. pugettensis dybovskyi and A. tzvetkovae. However, the new species can be distinguished from its congeners by several morphological differences, including the number of flagellar articles on antenna 1, the shape of robust setae on the palmar corner of gnathopod 1, the length of the coxal gill on pereopod 7, and the number of robust setae on the dorsal hump of urosomite 1. Additionally, nucleotide sequences of the mitochondrial cytochrome c oxidase subunit I (COI) confirm species level divergence. The other newly recorded species, A. pugettensis dybovskyi exhibits similarities with A. donghaensis sp. nov. and A. tzvetkovae. However, this species can be obviously distinguished from its congeners by the robust setal formula on urosomite 1, and dorsolateral tooth formula of urosomite 2. Both species are described and illustrated in the present study, along with a key to the species of genus Anisogammarus. This study represents the first record of the genus Anisogammarus from Korean waters.